2011
DOI: 10.1002/ar.21457
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression Nanog Activates Pluripotent Genes in Porcine Fetal Fibroblasts and Nuclear Transfer Embryos

Abstract: Nanog as an important transcription factor plays a pivotal role in maintaining pluripotency and in reprogramming the epigenome of somatic cells. Its ability to function on committed somatic cells and embryos has been well defined in mouse and human, but rarely in pig. To better understand Nanog's function on reprogramming in porcine fetal fibroblast (PFF) and nuclear transfer (NT) embryo, we cloned porcine Nanog CDS and constructed pcDNA3.1 (þ)/Nanog and pEGFP-C1/Nanog overexpression vectors and transfected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…It has been shown that overexpression of NANOG in donor cells had no effect on blastocyst rate in reconstructed embryos (Zhang et al, 2011). In our present study, similarly, the higher expression of NANOG in cloned AMSC-NT embryos could not improve the embryo development.…”
Section: Igf2 Igf2rcontrasting
confidence: 49%
“…It has been shown that overexpression of NANOG in donor cells had no effect on blastocyst rate in reconstructed embryos (Zhang et al, 2011). In our present study, similarly, the higher expression of NANOG in cloned AMSC-NT embryos could not improve the embryo development.…”
Section: Igf2 Igf2rcontrasting
confidence: 49%
“…Measurement of gene expression with quantitative real-time PCR has been applied in our previous research [19, 20]. Briefly, total RNA was extracted from 30 pooled embryos at each stage using an RNeasy Mini Kit (Qiagen, Dusseldorf, Germany) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that embryos cloned with highly expressed Oct4 cells enhanced blastocyst development, indicating that those cells underwent initial reprogramming events quite similar to normal fertilization (Pfeiffer et al, 2010). In embryos cloned with Nanog overexpression cells, Nanog overexpression did not have an effect on blastocyst rate or total cell number (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 98%